THE RITUAL OF KHANDURI LAÔT IN LOWLAND ACEH: An Ethnographic Study in South, South West and West Aceh - Abdul Manan (State Islamic University North Sumatra, 2016)
Abstract: This article aims to describe and analyze critically about the ritual of khanduri laôt in lowland Aceh. This annual ritual has been performed from one generation to another for it cannot be separated from the life of fishermen and it leaves a deep impression among the participants. This research is a field research and its data is obtained through meticulous observation of the ritual action and in-deep interview, discussion with the main protagonists of the ritual performance. The result of the research shows that the village fishermen made the offering (cosmological exchange) besides reciting the verses from the Qur’an. The offering is made to “the possessor of the fish” and is also given to “the sea water spirit” who takes care of the fish pond, the coast sea, the sea’s surface, the waves, and the deep sea. The village fishermen considered that cosmological exchange is important to be done as the protection for the fishermen from harm at sea besides the fish will go near the sea coast and taste the khanduri so that the fishermen can easily catch them. Abstrak: Ritual Kenduri Laut di Daratan Aceh: Kajian Etnografi di Aceh Selatan, Barat dan Baratdaya. Artikel ini bertujuan untuk mendeskripsikan dan menganalisa secara kritis tentang ritus khanduri laôt di dataran rendah Aceh. Ritus tahunan ini telah dilaksanakan dari generasi ke generasi karena tidak dapat dipisahkan dari kehidupan nelayan dan meninggalkan impresi yang mendalam diantara pengikutnya. Penelitian ini adalah penelitian lapangan dan datanya diperoleh melalui pengamatan terhadap aktivitas dan upacara ritus, wawancara mendalam dan diskusi dengan informan kunci. Hasil penelitian ini menyimpulkan bahwa nelayan desa membuat sesajian (pertukaran cosmos) selain membaca ayat-ayat al-Qur’an. Sesajian juga dibuat untuk the possessor of the fish, dan juga kepada the sea water spirit yang menjaga kolam ikan, pantai laut, permukaan laut, gelombang dan laut dalam. Nelayan-nelayan desa menganggap bahwa pertukaran kosmos perlu dilakukan sebagai proteksi bagi mereka dari gangguan di laut dan ikan akan pergi mendekat ke tepian dan memakan sesajian, sehingga nelayan bisa menangkapnya dengan mudah. Keywords: ritual of the khanduri laôt, sea water spirit, cosmological exchange